ANEKA TEKNIK PENYINGKATAN DALAM BAHASA SHORT MESSAGE SERVICE (SMS) - Ana Rosmiati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
The aim of this research is to find out the formal characteristics of SMS language. The population of this research was all of the utterances discovered in SMS language discourse from 2004 up to 2008. The utterances in SMS discovered in some cellular phones in Surakarta area were used as a sample for this research. The data were collected by listening to and interviewing some informants endorsed with a noting technique. SMS messages were directly sent to some participants to validate the data. The data were analyzed by using the equivalence (padan) pragmatic method to identify the forms and structures of the SMS language. The identity method was used to identify and classify lexical and grammatical aspects found in this discourse endorsed with deletion and substitution techniques. The results of the research showed that SMS language was a written discourse in the form of a dialogue between a speaker and an interlocutor making use of the facilities in cellular phones. The special characteristics of shortened words in SMS language included : (1) the omission of vowels, (2) the omission of consonants, (3) the omission of initial syllable, (4) the omission of final syllables, (5) contractions, (6) changes of diphthongs to vowels (‘monophthongization’), (7) the replacement of words by numbers, (8) the replacement of words by letters, and (9) the replacement of words by initial letters.